The Sagıttal And Vertıcal Changes Of Lıps Wıth Orthodontıc Treatment - Lale Taner-Sarisoy; Nilüfer Darendeliler (Galenos Yayinevi, 2001)
The aim of this study is to evaluate the changes in the upper and lower lips and to assess the relations between the dental structure and the lips of subjects treated with extraction of four first premolars and fixed mechanical orthodontic therapy. A total of twenty-five subjects were included in the study. Thirteen subjects snowed mesiodivergent and 12 showed hyperdivergent growth patterns. The comparison of the reply of the lips between the two groups after extraction orthodontic therapy, did not show any statistical significancy. According to the assessment of the correlation values after orthodontic therapy, vertical changes in Ls and Li were observed as the incisors changed in the vertical direction in the mesiodivergent group. Li and A' changed in the sagittal direction as the upper incisors were retruded and B', Ls, and Li changed in the sagital direction as the lower incisors were retruded. Li and Ls were retracted following upper incisor retrusion in the hyperdivergent group. Changes in the vertical direction in A', Ls, and Li were observed to be affected from upper incisor vertical changes and vertical changes in B' and Ls from lower incisor vertical changes. Changes were observed in the sagital direction in B', Ls, Li as a result of lower incisor retrusion. The results of the correlation analysis revealed that more values showed statistical significant changes as a result of the incisor retraction in hyperdivergent subjects. The reason for observing more correlation relationships in the hyperdivergent group whereas nonsignificant differences were obtained when the two groups were compared could be explained by the difference in the structure of the lips in subjects with hyperdivergent growth pattern.